2000
DOI: 10.7589/0090-3558-36.3.469
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Fluorescence Polarization Assay and Comparison to Other Serological Assays for the Detection of Serum Antibodies to Brucella Abortus in Bison

Abstract: A number of serological tests were compared for the detection of antibodies to Brucella abortus in bison (Bison bison). The performance of the fluorescence polarization assay (FPA) in both the preliminary evaluation and a subsequent blind validation indicated that this test was the most suitable for serological diagnosis of brucellosis in bison. The sensitivity and specificity in the preliminary evaluation were 92.1% and 99.4%, respectively. The sensitivity and specificity in a subsequent blind study were 96.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 11 publications
1
22
0
Order By: Relevance
“…We have recently described the use of FP assays, using a fluorescein-labeled OPS from Brucella abortus, for the detection of antibodies to Brucella spp. (a gram negative bacterium) in bovids, bison, cervids and swine [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. We have shown that this approach, in principle, can be applied to all gram negative bacteria, which possess OPSs, by extending it to the detection of antibodies to Salmonella spp.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…We have recently described the use of FP assays, using a fluorescein-labeled OPS from Brucella abortus, for the detection of antibodies to Brucella spp. (a gram negative bacterium) in bovids, bison, cervids and swine [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. We have shown that this approach, in principle, can be applied to all gram negative bacteria, which possess OPSs, by extending it to the detection of antibodies to Salmonella spp.…”
Section: Introductionmentioning
confidence: 88%
“…The assay was evaluated against a variety of commonly used assays (the buffered plate antigen test, the rose bengal plate test, the complement fixation test, the rivanol agglutination test, competitive ELISA, indirect ELISA and culture) in bovine sera [6,[10][11][12][19][20], porcine sera [13][14], bison sera [15], cervid sera [16], bovine whole blood [8,17,19], and bovine milk [8,18,19,21]. In all these studies the FPA was equal, and many times superior to the commonly used assays in terms of sensitivity and specificity, often achieving 99+% for both.…”
Section: The Fpa For the Detection Of Brucella Spp In Animal Body Flmentioning
confidence: 99%
“…petitive enzyme-linked immunoabsorbent assay, standard plate, and standard tube tests (Huber and Nicoletti 1986, Gall et al 2000, Nielsen and Gall 2001, Nielsen 2002, Philo and Edwards 2002. After 2000, serology status was determined by veterinarians or trained National Park Service biologists using the standard card or fluorescence polarization assay (Gall et al 2000, Nielsen andGall 2001).…”
Section: Seroprevalencementioning
confidence: 99%
“…We modeled uncertainty in data on exposure to brucellosis (section Seroprevalence) using a meta-analysis of studies of serological test sensitivity and specificity (Gall et al 2000, Nielsen and Gall 2001, Gall and Nielsen 2004. We estimated the parameters for the distribution of the probability of a true positive and the probability of a false positive using published values, aggregating results across tests (Table 3).…”
Section: Parameter Modelsmentioning
confidence: 99%
“…If a molecule is labelled, the rotation can be determined by measuring polarised light intensity in vertical and horizontal planes (19). It is host species-independent method and can be performed also with whole blood or milk (9,11,(20)(21)(22). According to OIE Terrestrial Manual 2009, the FPA is recommended as a prescribed test for bovine and porcine brucellosis for determining the health status of animals (19).…”
mentioning
confidence: 99%